2008
DOI: 10.1016/j.ccr.2008.04.001
|View full text |Cite
|
Sign up to set email alerts
|

TNFR1 Signaling and IFN-γ Signaling Determine whether T Cells Induce Tumor Dormancy or Promote Multistage Carcinogenesis

Abstract: No therapeutic cancer vaccine has yet shown sufficient efficacy to be approved in the U.S., in part because of the complex immune response to vaccination. A study in Cancer Cell helps refine the tactics for developing pancreatic cancer vaccines, showing that local activity by tumor-seeking helper T cells can retard-or promote-tumor development. 1 The study, conducted by a team led by Martin Röcken, professor of dermatology at Eberhard Karls University, could help cancer vaccine makers design therapies that dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
269
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(283 citation statements)
references
References 73 publications
7
269
0
7
Order By: Relevance
“…In line with this evidence, in this work, we demonstrated that DCs from mice immunized with Stat3Y705F-C4HD cells cocultivated with C4HD cells were able to upregulate CD86 and MHC class II molecules, markers of DC maturation. Importantly, tumor cells transfected with DN Stat3 vector or treated with JSI-124 released TNF-a and IFN-g, which can act synergistically to induce signaling in Ag-specific CD4 + T cells that prevents tumor angiogenesis, tumor cell proliferation, and multistage carcinogenesis (29). In addition, these cells produced RANTES, which is involved in T cell migration and NK cell recruitment to tumors (30), and IP-10, which is a chemoattractant for resting NK cells and activated T cells (31).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this evidence, in this work, we demonstrated that DCs from mice immunized with Stat3Y705F-C4HD cells cocultivated with C4HD cells were able to upregulate CD86 and MHC class II molecules, markers of DC maturation. Importantly, tumor cells transfected with DN Stat3 vector or treated with JSI-124 released TNF-a and IFN-g, which can act synergistically to induce signaling in Ag-specific CD4 + T cells that prevents tumor angiogenesis, tumor cell proliferation, and multistage carcinogenesis (29). In addition, these cells produced RANTES, which is involved in T cell migration and NK cell recruitment to tumors (30), and IP-10, which is a chemoattractant for resting NK cells and activated T cells (31).…”
Section: Discussionmentioning
confidence: 99%
“…It is clear from mouse models that adoptively transferred antigen-specific T cells are capable of eradicating established cancer (6)(7)(8), and the ability of CTLs to directly kill tumor and/or stromal cells is thought to be important for tumor elimination (9)(10)(11). Nonetheless, cytokines such as IFNg and TNFa produced by T cells are also likely to contribute to the prevention of tumor growth by ACT via mechanisms other than cell lysis (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Hermelink et al the adaptive tumor antigen specific T cells were found to arrest the growth of experimentally induced pancreatic tumors in mice in the presence of a coordinated interaction between IFN-γ and TNF. In the absence of this interaction [20]. In other studies also the IFNs have been suggested to provide a selective pressure that may lead to progression from elimination to equilibrium phase of the cancer immunoediting process [21].…”
Section: What Maintains the CI Equilibrium?mentioning
confidence: 99%